Assessment of immunization Status of Children between 12-23 months in Bareilly District - Joshi, Hari S; Gupta, Rakesh; Singh, Arun; Mahajan, Vipul (Nepal Journal of Epidemiology, 2011)
Objectives: To assess the immunization status of children in the age group 12-23 months and to know the reasons for non-immunization of children. Method: - A cross-sectional survey was conducted using WHO’s thirty cluster sampling technique in rural and urban areas of Bareilly district from August 2008 to January 2009. Rural areas were divided into blocks and blocks were divided into villages. Urban areas were divided into wards. Villages and wards were taken as clusters. During the house-to-house survey, a total of 240 children of age 12-23 months were included in the present study. Result: only around 50% of children were fully immunized while 27.5% were partially and 22.5 % were not immunized at all. Immunization coverage was highest for BCG (62.5%) and lowest for measles (39.2%). Dropout rates were 37.3%, 19.7% and 18.2% for BCG to measles, DPT1 to DPT3 and OPV1 to OPV3 respectively. Vitamin A prophylaxis showed a decline from 38.3 % to 16.7%. Amongst the various reasons for not immunizing the child, the most common in both rural (78.7%) and urban areas (28.6%) was lack of awareness for the need of vaccination. However in rural areas lack of availability of services (87.2%) was the major cause for not immunizing the child. Conclusion: The present study shows a low coverage of immunization and Vitamin A prophylaxis in both rural and urban areas. Important reasons for non-immunization were lack of awareness about vaccination and availability of immunization services in rural areas and urban areas. Key Words: Immunization coverage; Children between 12-23 months; Vitamin A Prophylaxis. DOI: http://dx.doi.org/10.3126/nje.v1i2.5091 Nepal Journal of Epidemiology 2011;1 (2):47-50